Utilization of Nanocellulose Fiber from Tapioca Industrial Solid Waste as a Bioplastic Filling Material - Wicaksono, Rumpoko; Wijayanti, Nur (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
This study aims to examine the properties of nanocellulose fibers produced from cassava through the acid hydrolysis process, as well as their potential use as a filler for bioplastics based on cassava starch (tapioca). The treatment of this research was acid hydrolysis process time consisting of 15 and 30 minutes and the use of nanocellulose fiber as a filler for bioplastics as much as 0%, 1%, 2%, and 3% w/w starch. The results of this study indicate that the diameter of the nanocellulose fibers produced is about 18-40 nm, good dispersion stability, the crystallinity index of the nanocellulose fibers produced by acid hydrolysis for 15 and 30 minutes are 39.7% and 31.2%, respectively. The addition of nanocellulose fibers can increase the tensile strength, but decrease its elongation ability.